Sebuah Hubungan Perilaku Hidup Bersih dan Sehat Rumah Tangga dengan Kejadian Diare di Desa Gunting Saga - Susanti, Nofi; Ikhwan, Ikhwan (Politeknik Kesehatan Kemenkes Mamuju, 2023)
The prevalence of diarrhea increased by 3% in South Kualuh Regency between 2019 and 2021. The hamlet of Gunting Saga Village, which serves as a study location, depends on the Kualuh River for their everyday requirements. The purpose of this study is to ascertain the correlation between the clean and healthy living behavior (PHBS) in household settings with the incidence of diarrhea in Gunting Saga Village. This quantitative study used analytical descriptive method with Cross-sectional design which was carried out in Gunting Saga Village, North Labuhan Batu District, North Sumatra Province in July 2022. A total of 57 housewives (IRT) were obtained with an age range of 23-66 years and an average high school education. Respondents were taken by snowball sampling technique using questionnaires that had been tested for validity (r-count>0.279[n=50]) and reliability (0.898>0.60). Data analysis used univariate and bivariate analysis, with IBM SPSS data processing software. The results showed that housewives in Gunting Saga Village had a good PHBS category in household settings (59.6%), only 36.8% of households experienced diarrhea. The highest PHBS category come from housewives aged 45-55 years old with Diploma (D3) education. While the lowest PHBS category comes from housewives aged 23-33 years old with non-school education. There was a significant association between PHBS in households with the incidence of diarrhea (p = 0.001 p < 0.05]) and educational characteristics of housewives (p = 0.001 p < 0.05]) and there was no significant association between housewives age and PHBS in households (p = 0.700 [p>0.05]). Puskesmas Gunting Saga can collaborate with the local community to form household-based PHBS posyandu cadres and conduct counseling consistently so that the incidence of diarrhea in Gunting Saga can be suppressed.